The association of physical activity, heart rate and sleep from an activity tracker with weight loss during a 6-month personalized combined lifestyle intervention: a retrospective analysis - Braem, C. I. R.; Pasman, W. J.; van den Broek, T. J.; Caspers, M. P. M.; Jagers, F. L. P. W.; Yavuz, U. S.; Hermens, H. J.; Veltink, P. H.; Wopereis, S. (BMC Digital Health, 2025)
Background Personalizing lifestyle interventions by self-monitoring with wearable sensors can enhance adherence and improve intervention outcomes. It is unknown whether measures from a wearable device can detect lifestyle changes during an intervention. Therefore, the association between individual weight loss with continuous measures from a Fitbit was examined during a personalized SLIMMER combined lifestyle intervention. Methods A retrospective analysis was performed to assess the association of various Fitbit (Charge 4) measures and self-monitoring behaviors on achieved weight loss during a personalized version of SLIMMER. In this study, 61 people with overweight or obesity were included and were followed one month before the start and six months during a personalized SLIMMER program. Personalization included ambulatory monitoring with an activity tracker and smart scale. Fitbit data was pre-processed to ensure sufficient day- and night- wear-time. Body weight was assessed at the study start and end. Physical activity (PA), heart rate, and sleep were selected from Fitbit output. Their mean change over time before and after the start of the intervention were evaluated with linear mixed effects models and their Spearman correlation with weight loss was investigated. Findings After pre-processing, 32 subjects with sufficient Fitbit data had 4.9% [1.7–7.7%] weight loss at the end of the program. Step count, moderate PA and vigorous PA increased before the intervention (1667 [0 – 3511] steps/day, p < 0.001, 38.6 [0.0 – 84.9] minutes/week, p < 0.05 65.6 [0.0 – 156] minutes/week, p < 0.05, respectively), but declined during the intervention (-465 [-1016 – 107] steps/day, p < 0.05, -28.6 [-40.4 – -16.1] minutes/week, p < 0.001, -22.0 [-38.2 – -4.2] minutes/week p < 0.05 respectively). Estimated mean resting heart rate (RHR) correlated moderately with weight loss before ( ρ = -0.46, p < 0.05) and during the intervention ( ρ = -0.53, p < 0.01). Weight loss correlated with the average number of at home weight measurements before ( ρ = 0.37, p < 0.05) and during the intervention ( ρ = 0.41, p < 0.05). Conclusions This study shows that participants increased physically active behavior before the lifestyle intervention, but this improvement was not maintained during the intervention. RHR is negatively correlated with weight loss before and during the lifestyle intervention and therefore suggesting that participants with a better physiological health status achieved more weight loss.